Locus‐specific concordance of genomic alterations between tissue and plasma circulating tumor DNA in metastatic melanoma. Issue 2 (7th December 2018) - Calapre, Leslie; Giardina, Tindaro; Robinson, Cleo; Reid, Anna L.; Al‐Ogaili, Zeyad; Pereira, Michelle R.; McEvoy, Ashleigh C.; Warburton, Lydia; Hayward, Nicholas K.; Khattak, Muhammad A.; Meniawy, Tarek M.; Millward, Michael; et al.
Abstract : Circulating tumor DNA (ctDNA) may serve as a surrogate to tissue biopsy for noninvasive identification of mutations across multiple genetic loci and for disease monitoring in melanoma. In this study, we compared the mutation profiles of tumor biopsies and plasma ctDNA from metastatic melanoma patients using custom sequencing panels targeting 30 melanoma‐associated genes. Somatic mutations were identified in 20 of 24 melanoma biopsies, and 16 of 20 (70%) matched‐patient plasmas had detectable ctDNA. In a subgroup of seven patients for whom matching tumor tissue and plasma were sequenced, 80% of the mutations found in tumor tissue were also detected in ctDNA. However, TERT promoter mutations were only detected by ddPCR, and promoter mutations were consistently found at lower concentrations than other driver mutations in longitudinal samples. In vitro experiments revealed that mutations in promoter regions of TERT and DPH3 are underrepresented in ctDNA. While the results underscore the utility of using ctDNA as an alternative to tissue biopsy for genetic profiling and surveillance of the disease, our study highlights the underrepresentation of promoter mutations in ctDNA and its potential impact on quantitative liquid biopsy applications. Abstract : This study by Calapre et al. critically appraised the concordance of the mutational profile of tissue and plasma biopsies prior to treatment, and the evidence of the impact of cfDNA biogenesis on the loci targeted for ctDNA quantification. Plasma ctDNA appears to be a reliable genetic material for mutational profiling of melanomas, allowing detection of clinically targetable mutations and longitudinal monitoring of late‐stage patients.